No extraction? No problem. Direct to PCR processing of tongue swabs for diagnosis of tuberculosis disease as an alternative to sputum collection - Charlotte L. Ahls; Duncan Emsweller; Seth J. Helfers; Xin Niu; Douglas Wilson; Leah R. Padgett; Paul K. Drain (Microbiology Spectrum, 2024)
ABSTRACT Sputum collection and testing for tuberculosis (TB) have been problematic due to the potential for aerosolization, difficulty in generating a quality sample, and complex DNA extraction methods. Tongue swabs are inexpensive, minimally invasive, and a promising alternative to sputum collection. We investigated the diagnostic accuracy of tongue swabs for TB diagnosis using the Truenat MTB Plus assay from Molbio Diagnostics with a direct to PCR processing method. Four tongue swabs were collected per participant using two nylon-flocked swabs and two spun polyester swabs. Following tongue swab sample collection, participants also provided two sputum samples, which were tested by Cepheid Xpert MTB/RIF Ultra or culture. Of the 81 participants enrolled, 24 (30%) were positive for TB disease by sputum Ultra. Using the Truenat MTB Plus test, tongue swabs had 54% (52/96) sensitivity and 99% (218/220) specificity compared to sputum Ultra. Crude lysate was also tested using an in-house qPCR assay, which allowed for increased sample input. Using this method, tongue swabs had 70% (67/96) sensitivity and 94% (216/224) specificity. Mycobacterium tuberculosis (MTB) sample quantification using digital PCR yielded between 20 copies (minimum) and 34,000 copies (maximum) of MTB per swab. In addition, serially collected tongue swabs resulted in similar levels of detected MTB, and spun polyester swabs performed equivalently to nylon-flocked swabs. Overall, this study demonstrates that tongue swab samples are compatible with the Truenat MTB testing platform and that a direct to PCR method is a viable diagnostic solution. IMPORTANCE Tuberculosis (TB) remains one of the world’s leading infectious disease killers, despite available treatments. Although highly sensitive molecular diagnostics are available, expensive equipment and poor infrastructure have hindered their implementation in low-resource settings. Furthermore, the collection of sputum poses challenges as it is difficult for patients to produce and creates dangerous aerosols. This manuscript explores tongue swabs as a promising alternative to sputum collection. While previous studies have explored the sensitivity of tongue swabs as compared to sputum, existing literature has not addressed the need to standardize and simplify laboratory processing for easy implementation in high TB burden areas. This manuscript provides the first evidence that detection of TB from a tongue swab is possible without the use of DNA extraction or purification steps. The data provided in this manuscript will improve the collection and testing of tongue swabs for the diagnosis of TB disease.